Hybrid Flexible Resistive Random Access Memory‐Gated Transistor for Novel Nonvolatile Data Storage. Issue 3 (18th November 2015) - Han, Su‐Ting; Zhou, Ye; Chen, Bo; Wang, Chundong; Zhou, Li; Yan, Yan; Zhuang, Jiaqing; Sun, Qijun; Zhang, Hua; Roy, V. A. L.
Abstract : Here, a single‐device demonstration of novel hybrid architecture is reported to achieve programmable transistor nodes which have analogies to flash memory by incorporating a resistive switching random access memory (RRAM) device as a resistive switch gate for field effect transistor (FET) on a flexible substrate. A high performance flexible RRAM with a three‐layered structure is fabricated by utilizing solution‐processed MoS2 nanosheets sandwiched between poly(methyl methacrylate) polymer layers. Gate coupling with the pentacene‐based transistor can be controlled by the RRAM memory state to produce a nonprogrammed state (inactive) and a programmed state (active) with a well‐defined memory window. Compared to the reference flash memory device based on the MoS2 floating gate, the hybrid device presents robust access speed and retention ability. Furthermore, the hybrid RRAM‐gated FET is used to build an integrated logic circuit and a wide logic window in inverter logic is achieved. The controllable, well‐defined memory window, long retention time, and fast access speed of this novel hybrid device may open up new possibilities of realizing fully functional nonvolatile memory for high‐performance flexible electronics. Abstract : A programmable transistor with a novel hybrid architecture is achieved by incorporating a resistive switching random access memory device and proposed as a resistive switch gate for field effect transistors on a flexible substrate. The controllable, well‐defined memory window, long retention time, and fast access speed of this device may open up new possibilities of realizing fully functional nonvolatile data storage for high‐performance flexible electronics.